Analysis of Dynamic Response and Fatigue Life of Masonry Pagoda under the Influence of Train Vibration - Qian Xia; Jin Zhao; Defa Wang; Yiqing Li (Advances in Civil Engineering)
Taking Liangxiang Pagoda built in Liao Dynasty in Beijing as the research object, the vibration responses of the pagoda in the east-west direction and south-north direction under the action of trains on the Beijing–Guangzhou Railway Line and microseism were tested. On this basis, a numerical model was established by using ANSYS to further calculate the dynamic response of the pagoda, and the safety and integrity of the pagoda were evaluated based on existing standards. Cumulative fatigue damage theory was introduced to predict the remaining fatigue life of Liangxiang Pagoda. The following conclusions have been drawn: in the two directions mentioned above, the natural vibration frequencies of the pagoda of the first three orders are similar; the 1st-order vibration modes in the plane are bending, and the vibration modes of the 2nd and 3rd orders are shear-bending; under the action of trains, the peak vibration value of Liangxiang Pagoda at the position that bears the maximum load is 0.053 mm/s, which has a little impact on the safety and integrity of the pagoda; under the combined action of gravity and trains, the remaining fatigue life of Liangxiang Pagoda is 5.26×107 times. The research method used in this paper can provide data and scientific support for the protection of historical buildings, as well as the basis for the follow-up research of the studied ancient pagoda.